2004
DOI: 10.1385/jmn:24:2:207
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinase Activation by Fluoxetine and Its Relation to Gene Expression in Cultured Rat Astrocytes

Abstract: Chronic treatments with antidepressants active on major depressive disorders influence pathways involved in cell survival and plasticity. As astrocytes seem to play a key role in the protection of brain cells, we investigated in these cells the rapid effects of the antidepressant fluoxetine (Prozac) on signaling cascades and gene induction, which probably play a role in neuroprotection. We show here that fluoxetine alone activates the extracellular signal-regulated-protein kinase (Erk) and p38 mitogen-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(92 citation statements)
references
References 46 publications
6
85
0
Order By: Relevance
“…This observation is consistent with the lack of alteration in the autophosphorylation of the TrkB Shc binding site, which mediates the activation of these signaling pathways (Saarelainen et al, 2003;Rantamäki et al, 2006). Previous studies on the role of MAPK pathway in the mechanism of antidepressant action have yielded conflicting results (Mercier et al, 2004;Tiraboschi et al, 2004;Fumagalli et al, 2005). The role of the pathways initiated by the TrkB Shc binding site have been extensively studied in vitro (Huang and Reichardt, 2001), but the replacement of the tyrosine 515 with a phenylalanine (which abolished the shc binding) in transgenic mice produced an unexpectedly mild phenotype (Minichiello et al, 2002), suggesting that other signaling pathways can largely compensate for the lack of MAPK pathway activation in vivo.…”
Section: Figuresupporting
confidence: 84%
“…This observation is consistent with the lack of alteration in the autophosphorylation of the TrkB Shc binding site, which mediates the activation of these signaling pathways (Saarelainen et al, 2003;Rantamäki et al, 2006). Previous studies on the role of MAPK pathway in the mechanism of antidepressant action have yielded conflicting results (Mercier et al, 2004;Tiraboschi et al, 2004;Fumagalli et al, 2005). The role of the pathways initiated by the TrkB Shc binding site have been extensively studied in vitro (Huang and Reichardt, 2001), but the replacement of the tyrosine 515 with a phenylalanine (which abolished the shc binding) in transgenic mice produced an unexpectedly mild phenotype (Minichiello et al, 2002), suggesting that other signaling pathways can largely compensate for the lack of MAPK pathway activation in vivo.…”
Section: Figuresupporting
confidence: 84%
“…Earlier studies have shown that phosphorylation at serine 505 of cPLA 2 protein by mitogenactivated protein kinase (MAPK p38) resulted in cPLA 2 activation. 53,54 Another study reported that fluoxetine activates MAPK p38 activity in cultured rat astrocytes, 55 which could account for the increased phosphorylation of cPLA 2 by chronic fluoxetine. The difference in the percent increase of cPLA 2 protein level (54%) compared to the percent increase in phosphorylated cPLA 2 (serine 505) level (27%) may represent differences in MAPK activity 54 and cPLA 2 protein half-life.…”
Section: Discussionmentioning
confidence: 99%
“…The current study indicates that decreased p38 MAPK activity is involved in functional changes observed in n-3 PUFA deprived rats. 15 Fluoxetine also activates the p38 MAPK cascade, 80 suggesting that the depressive symptoms observed in n-3 PUFA deprived rats are related to decreased p38 MAPK activity. Constitutive p38 MAPK activity maintains the expression of rat brain dopamine 81,82 and serotonin transporters 83 and n-3 PUFA deprivation upregulates D1 and D2 receptors 84 and decreases stimulated serotonin release, 85 all of which are believed to be involved in depression.…”
Section: Discussionmentioning
confidence: 99%